Iconic Attributes of Ergo-Iconic Value: A Synthesis for Sustainable Product Excellence - Andriyansah Andriyansah (International Journal of Economics Development Research (IJEDR), 2025)
Despite extensive research on ergonomics, aesthetics, and user experience, limited studies have integrated these perspectives to explain how iconic value is formed and sustained in the marketplace. This study aims to conceptualize the iconic attributes that constitute ergo-iconic value and to develop a novel theoretical framework through a systematic synthesis of literature indexed in Scopus and Web of Science. Drawing on theories of ergonomics, emotional design, aesthetics, value-based marketing, cultural branding, and the digital platform economy, the study constructs a comprehensive conceptual model of ergo-iconic value. The findings define ergo-iconic value as a superior value proposition derived from three dimensions of comfort: functional comfort, usability comfort, and pleasure comfort. Furthermore, three core iconic attributes are identified: symbolic and visual appeal, emotional connection and cultural identity, and economic activation and practical value. These attributes operate across visceral, behavioral, and reflective levels of user experience, consistent with Norman’s emotional design framework. The study further proposes the concept of Cultural Resonance Capital to explain why products, services, or digital content with comparable ergonomic and aesthetic qualities may exhibit different levels of market acceptance, consumer attachment, and longevity. As a conceptual study, the proposed framework requires empirical validation across diverse contexts. Nevertheless, it offers theoretical and practical insights for designers, marketers, and SMEs seeking to create sustainable value through the integration of functional performance, emotional engagement, and cultural resonance in the Industry 5.0 era.